Hygrothermal performance of wood-hemp insulation in timber frame wall panels with and without a vapour barrier. (October 2015) - Latif, Eshrar; Ciupala, Mihaela Anca; Tucker, Simon; Wijeyesekera, Devapriya Chitral; Newport, Darryl John
Abstract: An in situ experiment on a full-scale timber frame test building was carried out to study the hygrothermal performance of wood-hemp composite insulation in timber frame wall panels with and without a vapour barrier. The heat transfer properties and the likelihood of mould growth and condensation in the panels were compared. Step changes in the internal relative humidity were performed to explore the effects of high, normal and low internal moisture loads on the wall panels. No significant difference in the average equivalent thermal transmittance (U-values) between the panels with and without a vapour barrier was observed. The average equivalent U-values of the panels were close to the U-values calculated from the manufacturers' declared thermal conductivity values of the insulation. The likelihood of condensation was higher at the interface of the wood-hemp insulation and the oriented strand board (OSB) in the panel without a vapour barrier. In terms of the parametric assessment of the mould germination potential, the relative humidity, the temperature and the exposure conditions in the insulation-OSB interfaces of the panel without a vapour barrier were found to be more favourable to the germination of mould spores. Nonetheless, when the insulations were dismantled, no mould was visually detected. Highlights: Hygrothermal performance of wood-hemp insulation is assessed in a test cell. U-values of the wall panels with and without a vapour barrier are measured. U-values of the panels are lower than the calculated U-values. Moisture response is faster if the lining of the vapour open panel has low μ value. In situ observation does not support the prediction of interstitial mould growth.